Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1186/1472-6963-6-101
|View full text |Cite
|
Sign up to set email alerts
|

The influence of completing a health-related questionnaire on primary care consultation behaviour

Abstract: Background: Surveys of the population are commonly used to obtain information on health status. Increasingly, researchers are linking self-reported health status information to primary care consultation data. However, it is not known how participating in a health-related survey affects consultation behaviour. The objective of this study was to assess whether completion of a healthrelated questionnaire changes primary care consultation behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Previous studies have found that survey responders with the topic under investigation are more likely to consent to medical record access [39][41] or to consult [17]; however, there is also evidence that survey participants do not change their consulting behaviour after completing a health-related questionnaire [42]. By contrast, the evidence for differences in health between participants and non-participants in cohort studies of older adults shows that non-participation at follow-up is more likely in those reporting poorer health [4], [9], [12] and cognitive impairment [4], [10], [11], [43], which provides one explanation of the finding that baseline participants had been less likely to consult about depression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that survey responders with the topic under investigation are more likely to consent to medical record access [39][41] or to consult [17]; however, there is also evidence that survey participants do not change their consulting behaviour after completing a health-related questionnaire [42]. By contrast, the evidence for differences in health between participants and non-participants in cohort studies of older adults shows that non-participation at follow-up is more likely in those reporting poorer health [4], [9], [12] and cognitive impairment [4], [10], [11], [43], which provides one explanation of the finding that baseline participants had been less likely to consult about depression.…”
Section: Discussionmentioning
confidence: 99%
“…Previously it has been shown that postal surveys have no effect on subsequent consultation rates, either for the problem under focus or for other problems. 23 Further, people consenting to record review in this study had similar consultation rates to their whole-practice population. 24 Standardising the prevalence of insomnia for age and sex did not change observed rates, 1 and, while any selective non-response may affect the overall estimates of rates of consultation and prescription, the study's central analysis (the strength of association between baseline survey characteristics and subsequent consultation) is unlikely to be affected by any selection differences between participants, nonresponders, and non-consenters.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 84%